RETROSPECTIVE ANALYSIS OF THE AUDIT EMERGENCE AND DEVELOPMENT IN THE CONTEXT OF THE MODERNIZATION OF THE STATE FINANCIAL CONTROL SYSTEM - Obushna N.I. (Pressing Problems of Public Administration, 2016)
The article substantiates the need for establishment of the institute of public audit in the modernization of public administration in Ukraine. Systematized the main stages of formation and development of audits in the context of modernization of the state  nancial control. On this basis clari ed the content of public audit.